Dark Pulse Mode-locked Laser based on Aluminum Zinc Oxide coated D-shape fiber as Saturable Absorber. Issue 4 (2nd November 2021) - Nizamani, B.; Jafry, A. A. A.; Fizza, G.; Memon, F. A.; Salam, S.; Najm, M. M.; Abdul Khudus, M. I. M.; Hanafi, E.; Apsari, R.; Harun, S. W.
ABSTRACT: We have experimentally reported aluminum zinc oxide (AZO) as a novel saturable absorber to generate a mode-locked laser operating in dark pulsed regime. The D-shaped fiber was first prepared by side polishing a single-mode fiber to the 1 dB insertion loss. The AZO was dissolved in isopropyl alcohol and then deposited onto the D-shaped fiber by drop casting method. By carefully optimizing the polarization of the cavity, a dark pulse was achieved, which remained stable within the pump power of 65.7–101.35 mW. Pulse width was 220 ns, and the pulse repetition rate was 1.85 MHz.